Nuclear and Detector Sensitivities for Neutrinoless Double Beta-Decay Experiments - Hiroyasu Ejiri (Advances in High Energy Physics)
Neutrinoless double beta-decay (DBD) is of current interest in high-sensitivity frontiers of particle physics. The decay is very sensitive to Majorana neutrino masses, neutrino CP phases, right-handed weak interactions, and others, which are beyond the standard electroweak model. DBDs are actually ultrarare events, and thus, DBD experiments with ultrahigh sensitivity are required. Critical discussions are presented on nuclear and detector sensitivities for high-sensitivity DBD experiments to study the neutrino masses in the normal and inverted mass hierarchies.